The relationship of work stress and employee's job performance / Siti Shereena Azalea Mohd Azhar - Mohd Azhar, Siti Shereena Azalea (Faculty of Business And Management, 2016)
The purpose of this research to analyze variable of work stress toward the employee's job performance. Besides that, this research was carried out to examine the relationship between the work stress and employee's job performance. To obtain the result for this research, this research was conducted among staff in Enforcement Section at Ministry of Domestic Trade, Co-Operative and Consumerism (KPDNKK) Pahang. The 60 questionnaire was distributed as the method to collect the data for this research on work stress with employee's job performance at KPDNKK Pahang and used the Statistical Package for Social Science (SPSS) version 23.0 software as the tools to analyze the data for this study. Simple Random Sampling from probability sampling approach has been chosen. The objective of this study were achieved. As a conclusion, there will have another model of variable to make the relationship with the employee's job performance became strong and consistent. For the conclusion and recommendation, this study conclude the overall of the research. The recommendation involve for organization, employer and future research. The reliability of this study can be evaluated by using the correct instruments and more cautions should be taken by management. The future researcher can be aware about the work stress and employee's job performance.